Strategy for Strengthening Islamic Religious Education Curriculum in Forming Children's Islamic Character - Aura Mahdiyah; Juliani; Nia Nazlia; Nurul Arsih; Nurul Jannah (Yayasan Zia Salsabila, 2024)
Islamic Religious Education (PAI) plays a pivotal role in shaping students' Islamic character as a foundation for ethical and moral behavior aligned with Islamic values. This study aims to explore strategies for strengthening the PAI curriculum to foster Islamic character among students. A qualitative approach is employed, utilizing literature reviews, observations, and case studies to identify effective strategies. The findings highlight five key strategies: (1) integrating Islamic values into learning materials in Islamic Religious Education and Civic Education subjects; (2) habituating Islamic character values through daily school activities; (3) empowering extracurricular activities as a medium for internalizing Islamic principles; (4) establishing an Islamic school environment through exemplary behavior of teachers and school staff; and (5) monitoring and guiding students' behavior to ensure character development. These strategies are found to significantly enhance the formation of students' Islamic character, enabling them to navigate the challenges of globalization without compromising their moral identity. This research provides practical insights for educators and policymakers in designing and implementing an effective PAI curriculum.